Making income and property taxes more growth-friendly and redistributive in India - Joumard, Isabelle (OECD Economics Department Working Papers, 2017)
Tax reforms are crucial to promoting inclusive growth in India. The replacement of a myriad of consumption taxes by a Goods and Services Tax (GST) will boost India's competitiveness, investment, job creation and tax compliance. The potential to raise additional revenue from taxes on goods and services is however limited. In contrast, reforming income and property taxes should help to i) raise more revenue to finance much needed social and physical infrastructure while keeping public debt under control; ii) reduce inequality by increasing the redistributive effect of taxation; iii) promote productivity by reducing distortions in the allocation of resources which emanate from the corporate income tax; iv) boost job creation by eliminating the bias against labour-intensive activities; v) promote confidence, and thus investment, by improving clarity and certainty regarding tax rules and their application and vi) reinforce the ability of states and municipalities to provide key public infrastructure and services. This paper presents the main characteristics of the tax system as well as the rationale and options for reform